Machine vision beyond visible spectrum - Hammoud, Riad (Springer, 2011)
The material of this book encompasses many disciplines, including visible, infrared, far infrared, millimeter wave, microwave, radar, synthetic aperture radar, and electro-optical sensors as well as the very dynamic topics of image processing, computer vision and pattern recognition. This book is composed of six parts: Advanced background modeling for surveillance Advances in Tracking in Infrared imagery Methods for Pose estimation in Ultrasound and LWIR imagery Recognition in multi-spectral and synthetic aperture radar Fusion of disparate sensors Smart Sensors.